What features determine small states activities in the international arena? Iceland’s approach to foreign relations until the mid-1990’s - Baldur Þórhallsson (2005)
Fræðigrein The aim of this paper is to analyse the features that have determined Iceland’s international activity and to what extent Iceland has been an active participant in the international system. The paper focuses on the period from the time Iceland took full charge of the conduct of its foreign policy from Denmark in 1940 until 1994, fifty years after Iceland became a Republic and joined the European Economic Area (EEA). At the time of Iceland’s entry to the United Nations (UN) in 1946, it had the lowest population of all UN member states. Iceland soon joined most of the international organizations created in Europe and internationally after the Second World War. Iceland’s neighbouring states, the Nordic states, became pro-active within the UN and other international institutions, and the interesting question is to what extent Iceland, as a small newly-independent state, became involved in the international community. The paper aims to answer the following three questions. First, what domestic and international features have determined Iceland’s international activity? Second, has Iceland been reactive or pro-active in the international system? Third, did Iceland concentrate mainly on multilateral relations within international organizations, as the small-state literature generally claims is beneficial for small states, and as many states have done, or on bilateral relations in its international approach. The paper argues that Iceland was reactive in the international community and did not take an active part in international organizations such as the UN, NATO, EFTA, the World Bank and the Council of Europe in the period under study. Instead, Icelandic governments concentrated on bilateral relations with neighbouring states and important trading partners, i.e. the Nordic states, Britain and the United States (US), in terms of both defence and trade. The paper claims that Iceland’s international activity was characterized by the pursuit of self-determination throughout this period, despite the country’s ...